The Milano polarimeter: an instrument to search for large scale polarization of the Cosmic Microwave Background - ZANNONI, MARIO; BOELLA, GIULIANO FILIPPO; GERVASI, MASSIMO; PASSERINI, ANDREA; SIRONI, GIORGIO; Battistelli, E; Cavaliere, F (AIP Conference Proceedings, 2002)
The expected polarized component of the CMB signal is extremely faint. On degree angular scales and above it can be in the range of one part to 10 6 or 10 7. To detect such an elusive signal a dedicated instrument must be designed. We present the new Milano polarimeter, a 33-GHz correlation system able to detect both linear and circular polarization. It has been designed to operate at large angular scale (7deg-14deg) from the ground. In the light of the last observing campaign conducted from Antarctica we have partially redesigned the radiometer to improve its long term stability and sensitivity